Experience capitalization: What am I going to do to make this happen? - Watkins, Susan (Technical Centre for Agricultural and Rural Cooperation, 2019)
Before I arrived at the first workshop, I'd read through different things on the Internet to try and understand what Experience Capitalization was. I could see its value to my organisation immediately.